Is It Enough to Know That Tobacco Consumption Is Associated With Gastric Cancer? ¿Es suficiente saber que el consumo de tabaco está asociado con el cáncer gástrico? | 仅仅知道烟草消费与胃癌相关是否足够？ - Meza Gamboa, Oscar Gregory (2024)
I sincerely appreciate the publication of the article on the prevention of gastric cancer in patients from Lima, Peru. It is encouraging to see research that addresses crucial issues for public health, especially in our national context. Gastric cancer remains a global concern, with significant incidence and mortality, and tobacco consumption emerges as one of the most important risk factors after Helicobacter pylori infection. In Peru, the situation is no different. Despite efforts to combat this disease, the incidence and mortality from gastric cancer remain worryingly high. Recent data show that gastric cancer accounts for a considerable proportion of cancer deaths in our country. It is essential that gastric cancer prevention is prioritized, focusing on raising awareness about the risks of smoking and promoting healthy lifestyles. This requires not only financial resources, but also a coordinated and committed approach by health authorities and society as a whole. I hope this letter serves as a call to action to more effectively address gastric cancer prevention in Peru.